Acetylsalicylic Acid Inhibits IL‐18‐Induced Cardiac Fibroblast Migration Through the Induction of RECK. Issue 7 (July 2014) - Siddesha, Jalahalli M.; Valente, Anthony J.; Sakamuri, Siva S.V.P.; Gardner, Jason D.; Delafontaine, Patrice; Noda, Makoto; Chandrasekar, Bysani
<x xml:space="preserve">Abstract</x> The pathogenesis of cardiac fibrosis and adverse remodeling is thought to involve the ROS‐dependent induction of inflammatory cytokines and matrix metalloproteinases (MMPs), and the activation and migration of cardiac fibroblasts (CF). Here we investigated the role of RECK (reversion‐inducing‐cysteine‐rich protein with Kazal motifs), a unique membrane‐anchored MMP regulator, on IL‐18‐induced CF migration, and the effect of acetylsalicylic acid (ASA) on this response. In a Matrigel invasion assay, IL‐18‐induced migration of primary mouse CF was dependent on both IKK/NF‐κB‐ and JNK/AP‐1‐mediated MMP9 induction and Sp1‐mediated RECK suppression, mechanisms that required Nox4‐dependent H2O2 generation. Notably, forced expression of RECK attenuated IL‐18‐induced MMP9 activation and CF migration. Further, therapeutic concentrations of ASA inhibited IL‐18‐induced H2O2 generation, MMP9 activation, RECK suppression, and CF migration. The salicylic acid moiety of ASA similarly attenuated IL‐18‐induced CF migration. Thus, ASA may exert potential beneficial effect in cardiac fibrosis through multiple protective mechanisms. J. Cell. Physiol. 229: 845–855, 2014. © 2013 Wiley Periodicals, Inc.